An evidence-based system for the classification and clinical management of non-proximal gingival recession defects (2020)
Gingival recession defect (GRD) may be defined as an apical migration of the gingival margin respective to the cementoenamel junction resulting in partial exposure of the root surface to the oral cavity, which may have important esthetic, functional, and periodontal health implications. A novel system for the classification and management of non-proximal GRDs is proposed in this article. This evidence-based system consists of two essential components: (1) Establishment of the GRD type based on the midbuccal/midlingual attachment level respective to the interproximal bone level, and (2) Assessment of the gingival phenotype according to the width of attached gingiva and gingival thickness. Each category of this new classification system is linked with treatment recommendations substantiated by relevant literature pertaining to the outcomes of validated root coverage procedures in specific scenarios, which can be used as a guide for clinical decision-making in daily practice.